School-enterprise program, background of dual training: Case Universidad Tecnológica del Norte de Aguascalientes, Mexico - Rocha López, Marcela (2019)
The industrial sector demands higher education’s institutions to offer relevant study programs that can be applied and that can match the needs of this sector. One concrete action of the Universidad Technologica del Norte de Aguascalientes is the program School-Company, which was implemented in Accounting. It highlights the necessity of linking the academic contents to job activities. As a result of this linking, a skilled student is capable of applying the theoretical contents in the job area. The objective of this study was to identify the elements of Dual Education System and its application in Mexico thus determine the level of relation between this system and the UTNA program School-Company. To do this, it was necessary to describe the activities that UTNA accounting students carry out during the program in an accounting firm and how these activities match the academic contents. Students’ weekly reports were analyzed in order to identify the most frequent activities and their possible relation with the subjects of the career’s curriculum; as well as, the increase per year of the accounting firms, which agree on working in this program. The results showed that the most frequent activities are related to the theoretical and academic contents of the career’s curriculum.